Отбор членов команды в организации государственного управления - Леонтьева, Ольга; Труфанова, Валерия (Вопросы государственного и муниципального управления, 2018)
Public administration organisations in some countries, while focusing on project implementation through innovative approaches, are starting to apply an organisational matrix structure. This approach involves the adaptation of Lean in public administration by creating a model for rational project team members’ selection in public administration organisations. To examine this relatively new tool for public administration organisations, the authors base their research on the public administration organizations of Latvia and Russia and their employees by reporting the results of several studies. This interest in the Lean concept and its application in public administration, particularly in the sphere of human resource management activities, has been supported by the analysis of data retrieved from studies by the authors (primary quantitative and qualitative data analysis) and other researchers (secondary quantitative and qualitative data analysis) on public administration employees’ competences and personal preferences in Latvia and Russia. The article includes a comparison of personal preference identification concepts by various researchers (monographic research). Finally, the authors demonstrate the developed model, providing a detailed description and application guidelines. The authors conclude that the model’s application should be supported by its integration into a public administration employees’ performance assessment (by competences) system such as NEVIS which is used in Latvia. Public administration organisations can implement the proposed model, which is an example of the rational project team selection approach. The model considers both the competences and personal preferences of the potential project team members. The project team members’ selection process model also includes a mathematical decision-making model for solving optimisation tasks based on linear programming.